Menstrual Poverty in Egypt: Padding the Way to Period Equity - Hesham Nasr, Sara (AUC Knowledge Fountain, 2025)
With approximately 800 million women menstruating daily worldwide, a significant portion of this demographic experiences barriers to accessing sanitary products. In Egypt, despite having around third of the population in reproductive age and menstruating monthly, an economic turmoil in 2017 opted the government to label menstrual products as luxury items and the prices have increased since then. The current study aimed to investigate menstrual poverty in Egypt, focusing on the economic and social challenges faced by women during menstruation. Key objectives include assessing the financial challenges related to menstruation, exploring existing policies aimed at alleviating these challenges, and proposing evidence-based recommendations for public health policy to promote menstrual equity. The research employs a mixed-method approach, combining descriptive data analysis and qualitative insights through literature reviews and semi-structured interviews. Findings reveal that menstrual poverty significantly impacts women's physical, emotional, and social well-being. Nineteen Egyptian women from five different governorates were included in the study to represent different demographic and socioeconomic classes. The descriptive analysis showed that around 10% of salary is spent on menstrual related products and menstrual related issues such as missing workdays. While the qualitative thematic analysis highlighted the main issues such as the financial, educational and health impact. As participants reported salary deductions, missing school days and needing health interventions due to menstrual poverty. The study underscores the need for comprehensive strategies to address both the economic and societal dimensions of menstruation in Egypt, advocating for policy changes that ensure equitable access to menstrual hygiene products and education. As tackling menstruation poverty can aid in the economic and social progress of the Egyptian population.